2016
DOI: 10.1007/s00406-016-0760-z
|View full text |Cite
|
Sign up to set email alerts
|

Deficient amygdala–prefrontal intrinsic connectivity after effortful emotion regulation in borderline personality disorder

Abstract: ANOVA to test whether BPD patients exhibited weaker posttask increase in the amygdala intrinsic FC with the prefrontal cortex (PFC), compared to non-patients. Subsequently, we explored whether the results are common for personality disorders characterized by emotional problems, using additional data of 21 cluster-C personality disorder patients. In contrast to non-patients, BPD patients failed to show increased posttask amygdala resting-state FC with the medial, dorsolateral, ventrolateral PFC, and superior te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 76 publications
4
40
0
Order By: Relevance
“…Moreover, it has been reported that amygdala functional activations are lateralized to the left in emotional task-fMRI studies ( 52 ). In the BPD+CD− group, our results agree with previous studies that did not find differences in amygdala—mPFC functional connectivity compared with BPD−CD− ( 53 , 54 ). In the BPD−CD+ group we did not find a significant effect on functional connectivity, although it has been reported to be lower in CD compared to controls ( 20 ).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, it has been reported that amygdala functional activations are lateralized to the left in emotional task-fMRI studies ( 52 ). In the BPD+CD− group, our results agree with previous studies that did not find differences in amygdala—mPFC functional connectivity compared with BPD−CD− ( 53 , 54 ). In the BPD−CD+ group we did not find a significant effect on functional connectivity, although it has been reported to be lower in CD compared to controls ( 20 ).…”
Section: Discussionsupporting
confidence: 92%
“…The functional connection between these structures has also been suggested to facilitate the urgency to consume the substance of interest during abstinence in individuals with dependence, sending to a so-called "impulsive system", consisting of the amygdala and nucleus accumbens, signals that magnify the value of somatic marker representations (49). In the BPD+CD-group, our results agree with previous studies that did not find differences in amygdala -mPFC FC compared with BPD-CD- (50,51). Amigdala -mPFC FC has been reported to be lower in CD compared to controls (20), while we found it non-significantly higher.…”
Section: Discussionsupporting
confidence: 91%
“…Resting-state fMRI, contrasting intrinsic functional connectivity before and after an emotion regulation task in patients with BPD, further supports disrupted regulation of emotional circuits. Emotional hypersensitivity in BPD was associated with increased intrinsic connectivity between the amygdala and bilateral insula together with dorsal anterior cingulate cortex, while their impaired control over emotional reactions was associated with diminished intrinsic connectivity between the central executive fronto-parietal regions and salience network [ 68 ]. Overall the pattern of findings in relation to emotion regulation was similar to that reported for ADHD by Hulvershorn and colleagues [ 65 ].…”
Section: Overlap In Adhd and Bpdmentioning
confidence: 99%